The respiratory time and flow profile at volitional exercise termination - Kift, J.; Williams, E. M. (Journal of Sports Sciences, 2007)
In this study, we examine the effect of exercise on the time and flow characteristics of the respiratory cycle profile at the point of volitional exercise termination. Eight males (mean age 29 years, s = 10; body mass 74 kg, s = 7; height 1.75 m, s = 0.04) undertook a cycle test to volitional exhaustion on a cycle ergometer, which allowed peak oxygen uptake (O2peak) to be measured (mean 51 ml/kg·min, s = 7). At a later date, two sub-maximal tests to volitional exhaustion were completed in a random order at 76% (s = 6) and 86%O2peak (s = 7). As expected, the magnitude of the respiratory flow and time characteristics varied with the three exercise intensities, as did the point of exercise termination and terminal ventilation rates, which varied from 7 to 27 min and 112 to 132 l/min respectively. More importantly, however, at exercise termination some of the characteristics were similar, particularly the breathing frequency (at termination 49 breaths/min), the ratio between inspiration and total breath time (0.5), and the later occurrence of peak inspiratory flow (0.24 - 0.48 s). The coincident unity of these time and flow profile characteristics at exercise termination illustrates how the integration of timing and flow during breathing influence exercise capacity in non-elite athletes.